AGES INDUCE ECTOPIC ENDOCHONDRAL OSSIFICATION IN INTERVERTEBRAL DISCS - Illien-Jünger, S. (Eur Cell Mater, 2016)
Ectopic calcifications in intervertebral discs (IVDs) are known characteristics of IVD degeneration that are not commonly reported but may be implicated in structural failure and dysfunctional IVD cell metabolic responses. This study investigated the novel hypothesis that ectopic calcifications in the IVD are associated with advanced glycation end products (AGEs) via hypertrophy and osteogenic differentiation. Histological analyses of human IVDs from several degeneration stages revealed areas of ectopic calcification within the nucleus pulposus and at the cartilage endplate. These ectopic calcifications were associated with cells positive for the AGE methylglyoxal-hydroimidazolone-1 (MG-H1). MG-H1 was also co-localised with Collagen 10 (COL10) and Osteopontin (OPN) suggesting osteogenic differentiation. Bovine nucleus pulposus and cartilaginous endplate cells in cell culture demonstrated that 200 μg/mL AGEs in low-glucose media increased ectopic calcifications after 4 d in culture and significantly increased COL10 and OPN expression. The receptor for AGE (RAGE) was involved in this differentiation process since its inhibition reduced COL10 and OPN expression. We conclude that AGE accumulation is associated with endochondral ossification in IVDs and likely acts via the AGE/RAGE axis to induce hypertrophy and osteogenic differentiation in IVD cells. We postulate that this ectopic calcification may play an important role in accelerated IVD degeneration including the initiation of structural defects. Since orally administered AGE and RAGE inhibitors are available, future investigations on AGE/RAGE and endochondral ossification may be a promising direction for developing non-invasive treatment against progression of IVD degeneration.